Barbados. Significant achievements 2021 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Barbados during 2021 are identified, with respect to the needs and interests of the country, strengthening is issues of agribusiness, apiculture, composting, bioeconomy, agrotourism, technology and food safety and sanitation. Likewise, alliances were created between the public and private sectors, strategic plans for innovation in agriculture and to promote local commerce, and a manual of protocols for dealing with COVID-19. Finally, work was done on the resurgence of papaya production and on promoting agroscience students for their training and certification.